Détermination des facteurs de risque et des complications liées au développement de l'ictère néonatal chez des nouveau-nés de la région de Mostaganem - Oualid, Amel; Saaidia, Sarah (My University, 2021)
Neonatal hyperbilirubinemia is due to the easy production of bilirubin and the limited excretion capacity of newborns. Infants have higher levels of bilirubin production than adults, especially premature infants, due to their higher turnover rate and shorter lifespan of red blood cells. The objective of this work is to determine the main risk factors as well as the complications related to the development of neonatal jaundice in newborns in the region of Mostaganem. For this, 30 unselected newborns (sex ratio F / G, 14/16) of average age between 0 to 7 days with neonatal jaundice were followed. The study was carried out at the Neonatal Department of Lalla Kheira Maternity Hospital (Mostaganem) over a period of 1 month (from April 3 to May 5, 2021). The general characteristics of the jaundice population were determined. A total, direct and indirect bilirubin assay was performed. We also performed C-reactive protein, SNSF, blood count, transaminases, urea, creatinine, prothrombin, TCK, and blood group assays. Our results show: • A high rate of total, direct and indirect bilirubinemia in the 30 cases studied. • A male predominance (53.33%) with a sex ratio of 1.14 in favor of the male sex. • 43.33% of cases were premature newborns weighing less than 2500g versus 53.33% who had normal weight (2500g-3000g). • The mean maternal age of jaundiced infants was 28 years with a predominance of cesarean delivery (57%). • A slight increase in hemoglobin, hematocrit and red blood cells. • ABO erythrocyte incompatibility with a greater proportion of O / O incompatibility. • A decrease in PT in 66.67% of cases as well as a slight increase in TCK. • A decrease in creatinine and urea. • A high level of transaminases. • 33.33% of jaundiced newborns had a positive CRP. All of these results show that the development of neonatal jaundice is associated with several risk factors and that this condition could be linked to several hepatic and renal disturbances or even coagulation problems.
Keywords: Bilirubin, Coagulation, CRP, Risk factors, Hyperbilirubinemia, Jaundice.